One small step in frailty research, a giant leap in evidence based practice - Apóstolo, João; Bobrowicz-Campos, E.; Holland, Carol; Cano, Antonio (JBI Database of Systematic Reviews and Implementation Reports, 2018)
Demographic aging represents one of the greatest challenges in sustainability and efficiency of health and social care systems, requiring a fundamental shift in health policy at national and regional levels. Concerned international agencies, such as the World Health Organization (WHO) and the European Innovation Partnership on Active and Healthy Ageing (EIP on AHA), have developed action plans aimed at supporting the accessibility of the benefits of increased life expectancy to older people.